Place perception and restorative experience of recreationists in the natural environment of rural tourism - Tang, Ruomei; Zhao, Xinyu; Guo, Zixi (Frontiers in Psychology, 2024)
In the high-pressure environment in which the contemporary population is exposed to for a long time, tourism has become the main way to relax and escape from the daily environment, and tourism activities have gradually been internalized as a new type of means of self-recovery, stress release and spiritual liberation. The quality of the environment in tourist destinations has become the main basis for the choice of tourist destinations for the general public. In recent years, scholars have expanded and deepened the content of related research from the perspectives of different levels of blue-green space, natural elements, etc., and constantly tried to utilize new experimental means, with remarkable results. Rural natural scenes have a better recovery effect than other scenes(Li, Yuan, Sun, & Sun, 2022), and rural environments can also give tourists deep spiritual and psychological satisfaction on top of providing visual appreciation and other types of experiences. Therefore, this paper starts from the relationship between rural place perception and restorative experience evaluation, based on the restorative environment theory and other theories, and focuses on whether rural environmental factors have a restorative effect on tourists by collecting 300 questionnaires and analyzing with the structural equation modeling in SPSS26.0. It was found that the degree of rural nature perception has a positive correlation with place attachment and restorative experience. The analysis of the study led to the conclusion that focusing on different attribute perceptions and levels of place attachment in rural environments can enhance restorative experiences of tourists in rural environments.